Evaluation of competences for research through experimental reports: An example with high school professors - Maria Elena Rodriguez Perez; Catalina Rodríguez Pérez; Luis Hernando Silva Castillo (Interacciones)
In this paper, the concept of competence is described according to interbehavioral psychology signaling the superiority of this approach in comparison to cognitive and behavioral models. A competence, in the interbehavioral approach, refers to the functional organization of skills in order to fulfill a type of performance criterion. To illustrate the use of this notion in educational settings, an evaluation of research competences was carried out through the analysis of 17 research reports prepared by high school professors of the University of Guadalajara. Four competences were identified considering research as a case of theoretical modulation of intervention of reality. Five types of performance criteria were described for each competence using the Ribes y Lopez (1985) taxonomy as a model. An evaluation instrument was also developed which it was used by two judges to independently evaluate the experimental reports. Results suggested that the authors of the reports could not critically use theoretical referents. Only few reports showed correspondence between data analysis and conclusions. Pros and cons of the evaluation methodology used in this work are discussed in order to outline a strategy to assess and brief research reports.